The Association between Intimate Partner Violence and Functional Gastrointestinal Disorders and Symptoms among Adult Women: Systematic Review - Banjar, Ohud (Journal of family violence, 2022)
Functional gastrointestinal disorders (FGIDs) and symptoms have been identified as possible health consequences of intimate partner violence (IPV). However, whether specific types of abuse (i.e., psychological, physical and sexual) are associated with FGIDs and the implications of FGIDs for women’s quality of life (QOL) in the context of IPV are not well understood. This systematic review examined the association between the different types of IPV and the risk of FGIDs and symptoms among adult women and assessed the impact of FGIDs and symptoms on women’s QOL. Seven electronic databases were searched using the following criteria: English language studies of adult women (15 years or older) who had experienced IPV and reported FGIDs and symptoms; both quantitative and qualitative studies were included, and no time frame for publication was specified. A total of 15 studies (14 quantitative, 1 qualitative) conducted in 9 countries satisfied our inclusion criteria. IPV was associated with increased odds (1.6 to 2.7) of reporting a FGID. Each type of IPV (physical, sexual, psychological) was associated with FGIDs, alone or in combination. FGIDs were associated with some aspects of women’s QOL in the context of IPV (specifically seeking health care). Attention to the association between IPV and FGIDs could help strengthen health care for women who have experienced IPV and are suffering from FGIDs and inform future research to understanding this association in more depth.